EKSPLORASI BENTUK & FAKTOR PENDORONG PERILAKU KONSUMSI BERTANGGUNG JAWAB LINGKUNGAN DI YOGYAKARTA - Kristia Kristia; Banu Badrika (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the forms of environmentally responsible consumptiom and the driving factors that influence the informants in Yogyakarta. The research method used is a qualitative study through in-depth interviews with 20 participants who identify themselves as consumers who are responsible for the environment. The interview data are processing using ATLAS.ti program assistance. The four primary forms of environmentally responsible consumption behavior included purchasing environmentally friendly products, reducing consumption behavior, recycling, and reuse. Those behaviors are mainly influenced by internal factors and supported by external factors. Various stakeholders can use the results of this research to understand and design strategies to improve responsible consumption behavior patterns in society.